Municipal joint bean seed production system in Veracruz, Mexico. - Ugalde-Acosta, Francisco Javier (2014)
The objective was to evaluate bean seed yield as a local craft production system (FSAP-Municipal), in order to promote rural development through the use of high quality bean seed, as well as to improve crop productivity in 23 municipalities of the South-Central and High Mountains regions of Veracruz State, Mexico. The strategy was implemented from 1998 thru 2010 including two phases: first, establishment of varieties test plots to select the highest productivity ones, and then grow craft seed production plots. During the validation in the South Central region, bred varieties exceeded 78.7% to the control Black Michigan (743 kg/ha). In the High Mountains, bred cultivars reached 1219 kg/ha yield, while Black Michigan was 751 kg/ha. The selected varieties were Black Tropical, Black INIFAP and Black Veracruz. A total 28 300 kilograms of bean seed were obtained in 628 hectares, which benefited 1545 producers. The average yield increase of bean seed obtained by farmers in the FSAP-Municipal system was 109.4% higher compared to local varieties.